2015
DOI: 10.1007/s00246-015-1251-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prostaglandin E1 Infusion for Newborns with Critical Congenital Heart Disease

Abstract: Prostaglandin E1 is crucial for keeping the patent ductus arteriosus in critical congenital heart disease for the survival and palliation of particularly prematurely born babies until a cardiosurgical intervention is available. In this study, the side effects of prostaglandin E1 in newborns with critical congenital heart disease and clinical outcomes were evaluated. Thirty-five newborns diagnosed with critical congenital heart disease were treated with prostaglandin E1 between January 2012 and September 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…23 However, many of these side effects are manageable and should not deter clinicians from using PGE1 in newborns with CHD. 23 In cases of TA with reduced PBF and cyanosis, patients may also undergo surgery to have a polytetrafluoroethylene conduit fitted between the right subclavian artery and right pulmonary artery. 27 This is known as a modified Blalock-Thomas-Taussig shunt (MBTS) and like PGE1, it also enables temporary mixing of the systemic and pulmonary circulations.…”
Section: Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…23 However, many of these side effects are manageable and should not deter clinicians from using PGE1 in newborns with CHD. 23 In cases of TA with reduced PBF and cyanosis, patients may also undergo surgery to have a polytetrafluoroethylene conduit fitted between the right subclavian artery and right pulmonary artery. 27 This is known as a modified Blalock-Thomas-Taussig shunt (MBTS) and like PGE1, it also enables temporary mixing of the systemic and pulmonary circulations.…”
Section: Classificationmentioning
confidence: 99%
“…These take a significant amount of time and resources to organize. Prostaglandin E1 (PGE1) can therefore be given in the meantime to maintain a PDA 23 . This is a potentially life‐saving intervention in cases of TA with reduced PBF, as these infants rely on a PDA for the pulmonary and systemic circulations to mix 24 .…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Alprostadil is a stable prostaglandin E 1 analogue that demonstrates activity inhibiting platelet aggregation, relaxing smooth muscle of peripheral blood vessels, anti-oxidation, endothelium protection and stabilizing liver cell membrane [1][2][3][4]. For this reason, intravenous or intraarterial administration has been successfully used in the management of critical leg ischemia, angiospastic disorders, Raynaud's phenomenon, diabetic peripheral neuropathy, diabetic foot, liver transplantation, etc [5][6][7][8]. The conventional preparation of alprostadil has a half-life of only 3-5 minutes and is metabolized rapidly, so constant administration is required.…”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandin E1 (PGE1), is a pivotal member of the prostaglandin family which are cyclic, oxygenated fatty acids that exert diverse and powerful effects on cell function in many organ systems [1,2]. As a product of arachidonic acid metabolism by cyclooxygenase, PGE1 is associated with pro-and anti-inflammatory actions [2], osteoporosis, and some studies have found PGE1 could reduce the compression trauma-induced spinal cord injury and had beneficial effect on osteoporosis management [3,4]. Additionally, PGE1, as a potent vasodilator, has beneficial hemodynamic effects on patients with severe heart failure by increasing cardiac output and decreasing filling pressures and pulmonary vascular resistance [5].…”
Section: Introductionmentioning
confidence: 99%